2013
DOI: 10.1371/journal.pbio.1001616
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Differentiation under Mixed Culture Conditions Reveals a Tunable Continuum of T Cell Fates

Abstract: An experimental and theoretical study of T cell differentiation in response to mixed-input conditions reveals that cells can tune between Th1 and Th2 states through a continuum of mixed phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 55 publications
10
96
0
Order By: Relevance
“…However, this notion is challenged by evidence of population heterogeneity (29)(30)(31)(32) and Th cell plasticity (33)(34)(35)(36)(37), showing that, under various conditions, differentiated cells can adopt hybrid phenotypes, coexpressing signature TFs and cytokines of different lineages. We and others have recently shown that naïve CD4 + T cells can differentiate into a mixed Th1-Th2 phenotype, coexpressing lineage-specific TFs and cytokines of both cell types in varying levels depending on the relative levels of input cytokine signals (38)(39)(40). Taken together, these observations suggest a more complex picture of CD4 + T-cell fate determination with a substantial degree of phenotype plasticity and flexibility in response to different input stimuli.…”
Section: Significancementioning
confidence: 68%
See 4 more Smart Citations
“…However, this notion is challenged by evidence of population heterogeneity (29)(30)(31)(32) and Th cell plasticity (33)(34)(35)(36)(37), showing that, under various conditions, differentiated cells can adopt hybrid phenotypes, coexpressing signature TFs and cytokines of different lineages. We and others have recently shown that naïve CD4 + T cells can differentiate into a mixed Th1-Th2 phenotype, coexpressing lineage-specific TFs and cytokines of both cell types in varying levels depending on the relative levels of input cytokine signals (38)(39)(40). Taken together, these observations suggest a more complex picture of CD4 + T-cell fate determination with a substantial degree of phenotype plasticity and flexibility in response to different input stimuli.…”
Section: Significancementioning
confidence: 68%
“…To test this assumption, we attempted to populate the region in between Th1 and Th2 phenotypes in the differentiation space using varying concentrations of two input cytokines, IL-12 and IL-4. As we have previously shown (38), gradually changing concentrations of IL-12 and IL-4 result in mixed Th1-Th2 phenotypes. (Fig.…”
Section: The Segmented Linear Model Predicts Trajectories In the Diffmentioning
confidence: 74%
See 3 more Smart Citations